1998
DOI: 10.1111/j.1651-2227.1998.tb01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of season and discharge weight on complications and growth of Kangaroo Mother Care treated low birthweight infants in Mozambique

Abstract: This study aimed to determine the impact of season and weight at discharge on growth rate and complications in low birthweight infants treated with Kangaroo Mother Care (KMC) in Maputo, Mozambique. The study population included 246 infants of birthweight < 2000 g. Follow‐up until 2400 g was obtained in 64%. There were no seasonal differences in weight gain and the risk of complications of infants treated with KMC in hospital. During the cold season after discharge, the risk of serious complications, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Our use of a low-reading thermometer and a more inclusive definition of hypothermia (<36.51C), as well as lower ambient winter temperatures in the study area, may explain, in part, the higher rates of hypothermia reported in our study. Lincetto et al 28 found that the risk of complications after discharge of newborns who had been managed in the hospital with KMC was greater in the cold season, which they attributed to exposure to low ambient temperatures. Baby is more relaxed while listening to mother's heartbeat Mothers were advised to practice STSC for as long and as often as possible, but were not given a prescription but rather were given freedom to adapt the practice to their lifestyle No perceived adverse effects…”
Section: Newborn and Maternal Hypothermiamentioning
confidence: 99%
“…Our use of a low-reading thermometer and a more inclusive definition of hypothermia (<36.51C), as well as lower ambient winter temperatures in the study area, may explain, in part, the higher rates of hypothermia reported in our study. Lincetto et al 28 found that the risk of complications after discharge of newborns who had been managed in the hospital with KMC was greater in the cold season, which they attributed to exposure to low ambient temperatures. Baby is more relaxed while listening to mother's heartbeat Mothers were advised to practice STSC for as long and as often as possible, but were not given a prescription but rather were given freedom to adapt the practice to their lifestyle No perceived adverse effects…”
Section: Newborn and Maternal Hypothermiamentioning
confidence: 99%
“…Since the introduction of KMC more than 30 years ago in Bogotá Colombia, different forms of KMC practice have spread across the world. In the 1980s and 1990s, KMC was introduced in African countries such as Ethiopia [5], Mozambique [6], South Africa [7], and Zimbabwe [8,9], mostly in teaching hospitals with no further scale-up to lower levels of care.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that compared to newborns who do not have SSC with their mothers, newborns with SSC have more stable temperatures, heart rates, respiratory rates, and gastrointestinal adaptation (Bauer, Sontheimer, Fischer, & Linderkamp, 1996;Cleary, Spinner, Gibson, & Greenspan, 1997;Conde-Agudelo, Diaz-Rossello, & Belizen, 2000;Fohe, Kropf & Avenarius, 2000;Ludington-Hoe, Anderson, Swinth, Thompson, & Hadeed, 2004;Moore, Anderson, & Bergman, 2007). The infants' sleep is more restful (Feldman & Eidelman, 2003;Messmer et al, 1997), they cry less (Christensson et al, 1992;Christensson, Cabrera, Christensson, Uvnas-Moberg, & Winberg, 1995;Ferber & Makhoul, 2004;Michelsson, Christensson, Rothganger, & Winberg, 1996), grow faster (Bergman & Jurisoo, 1994;Lincetto et al, 1998;Rojas et al, 2003), breastfeed longer (Charpak, Ruiz-Pelaez, Figueroa, & Charpak, 2001;Meyer & Anderson, 1999), experience less pain from routine procedures (Gray, Miller, Philipp, & Blass, 2002;Gray, Watt, & Blass, 2000), and go home sooner from the hospital (Cattaneo et al, 1998;Charpak, Ruiz-Pelaez, Figueroa, & Charpak, 1997;Charpak et al, 2001), thereby saving money for hospitals and health systems. Most of the research on the benefits of SSC to infants has been conducted exclusively in the newborn period.…”
mentioning
confidence: 99%